Gastric acid suppressants and cognitive decline in people with or without cognitive impairment - Che‐Yuan Wu; Lisa Y. Xiong; Michael Ouk; Jennifer S. Rabin; Nathan Herrmann; Krista L. Lanctôt; Moira K. Kapral; Marcus Law; Hugo Cogo‐Moreira; Jodi D. Edwards; Walter Swardfager (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2022)
Abstract Introduction Studies suggest associations between proton pump inhibitors (PPIs) and dementia risk; however, many neither considered histamine‐2 receptor antagonists (H2RAs) nor baseline cognitive status. Methods Participants (National Alzheimer's Coordinating Center Database; 2005–2021) using a PPI or H2RA were compared. Covariate‐adjusted Cox regression was used to estimate hazard ratios (HR) for progression from normal cognition to mild cognitive impairment (MCI), and from MCI to dementia over 5 years. In a propensity‐score–matched subsample of mild–moderate Alzheimer's disease (AD), mixed‐effects negative binomial regression was used to estimate decline in delayed recall memory. Results Compared to PPI, H2RA use was associated with earlier progression from MCI to dementia (HR = 1.40 [1.09–1.81]; n = 1701), and with faster memory decline in AD over time (rate ratio = 0.76 [0.64–0.92]; n = 628), but not with progression from normal cognition to MCI (HR = 0.94 [0.71–1.24]; n = 2784). Discussion Compared to PPIs, H2RAs were associated with cognitive decline, specifically among people with pre‐existing cognitive impairment.